A preliminary research on transcultural capacity in global public health: from the view of public health professionals - Feng Ning; Liu Xin; Wang Quan; Liang Xiaohui; Dong Xiaoping (BMC, 2023)
Abstract Background Transcultural capacity is a key component of consolidated global public health assistance cooperation (GPHAC). The aim of this study is to investigate the transcultural capacity perceptions of public health professionals from China's disease control and prevention system after relative training in order to provide a reference for enhancing transcultural capacity during the practice of GPHAC. Methods A cross sectional qualitative survey in which self-administrated questionnaire with 5 open ended questions was used. The questionnaire was disseminated on the completion of an online training for China's senior public health professions on transcultural capacity in GPHAC. Descriptive statistics, word frequency analysis and content analysis were used to analyze the questionnaire data. Results Totally, 45 participants took part in this training, 25 of them voluntarily participated in this survey. The participants demonstrated the need for transcultural competence in public health services and suggested improvement in the course content arising from their wealth of knowledge and practical experience in the field. 96% of the participants considered that the training course was "very necessary" and "meaningful". The most interested topics were "Overview of transcultural adaptation and GPHAC", "Transcultural adaptation and response" and "African culture and health". The contents about "Country-specific analysis on cultural factors in public health", "rapid transcultural adaptation" and "more specific practical experiences in diverse cultural backgrounds" were suggested to be added in future training. The participants considered that transcultural capacity ensured the smooth progress of GPHAC and they both could complement each other, transcultural adaptation was the premise of gaining trust and reaching cooperation, it can be conducive to the health assistance professionals to integrate into local cultural life, facilitating their foreign assistance work to be effective and efficient, and impart experiences well. The participants hoped to put the concept into action. Conclusion The importance of transcultural competence in GPHAC is becoming a consensus of public health professionals. Enhanced transcultural competence reflected in the attitude of public health as well as other health workers would promote GPHAC and would foster efficient emergency health response management among many countries.